Validity and reliability of the turkish version of the early activity scale for endurance in preschool children with cerebral palsy. (17th February 2023) - Dere, Tuğba; Serel Arslan, Selen; Alemdaroğlu-Gürbüz, İpek
ABSTRACT: This study presented the Turkish translation of the Early Activity Scale for Endurance (T-EASE) which was developed to evaluate the endurance for physical activity of preschool children with Cerebral Palsy (CP), and its validity and reliability. Fifty-five children with CP aged between 2 and 5 years were included in the study. The Gross Motor Function Classification Scale (GMFCS) and Pediatric Outcomes Data Collection Instrument (PODCI) were used to determine motor function levels and quality of life of the study population. The T-EASE had good test-retest reliability (ICC = 0.996), internal consistency (α = 0.903), higher construct validity approved by confirmatory factor analysis, and criterion validity supported by the weak-to-strong correlations between T-EASE and GMFCS, and PODCI. The T-EASE scores were significantly different between GMFCS levels (p < .05). The T-EASE was found to be valid and reliable to determine the endurance for physical activity of Turkish pre-school children with CP with the sensitivity to changes in motor function levels.